" مشروعية التحكيم في منازعات العقود الإدارية في ضوء الأنظمة العربية – دراسة مقارنة " - إعداد/ د. أماني فوزي السيد (مجلة العلوم الشرعية, 2018)
" مشروعية التحكيم في منازعات العقود الإدارية في ضوء الأنظمة العربية – دراسة مقارنة "